Melindungi Integritas Data: Audit Kepatuhan Cobit 5 Untuk Sistem Accurate 5 - Eka Putri, Aliffia; Agus Prasetyo Utomo; Mariana, Novita (Institut Informatika Dan Bisnis Darmajaya, 2025)
This study aims to assess the effectiveness and compliance level of information security controls in the Accurate 5 system using the COBIT 5 framework. The evaluation focuses on data protection mechanisms such as access management, encryption, and activity monitoring, which are aligned with the COBIT 5 domains (APO, BAI, DSS, and MEA). Data were collected through a 13-item questionnaire, interviews, and system documentation analysis. The results indicate that the effectiveness of security controls achieved an average score of 4.18, while compliance with COBIT 5 reached an average score of 4.08. This study contributes by providing a practical compliance audit model for IT-based organizations to enhance data integrity and strengthen information security governance.